About types of arachnids (Araneae, Opiliones, Pseudoscorpiones) described by E. Schenkel from China in 1953 - Marusik, Yuri M.; Li, Shuqiang (Zootaxa, 2011)
The Swiss arachnologist Ehrenfried Schenkel published three large works concerning Chinese spiders and other arachnids (Schenkel 1936, 1953, 1963) in which he described over two hundred species belonging to different families. Material from the first work (Schenkel 1936) is preserved in the Natural History Museum in Stockholm and was partly redescribed by several authors. The same is true for the spiders described in 1963. Most of the material from this publication is in Paris and has been partly revised. The first and last papers were published in the Stockholm and Paris museum proceedings. The second paper (Schenkel 1953) appeared in the Boletim do Museu Nacional (Rio de Janeiro, Brazil), while the material was cited as being from the “Museum Hoangho-Peiho” in Tientsin [= Huanghe (Yellow River) and Baihe (Haihe River) and Tianjin in modern English respectively]. This work dealt with 59 species of spiders, harvestmen and pseudoscorpions. Forty of them were described as new species and six as a new subspecies. One of the harvestmen species was described in a new genus. Forty new taxa belong to spiders, one to pseudoscorpions and five to harvestmen. All specimens were collected in central and northern China. Several new species were described from the center of Beijing. None of the types from this publication have since been studied. While trying to find some of the types two decades ago, the first author heard from some colleagues that the material was destroyed during shipment back to China.